2021
DOI: 10.1177/15248380211030250
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Homicide in Community-Dwelling Older Adults: A Systematic Review and Meta-Analysis

Abstract: Background: Empirical research investigating older adult homicide is sparse and rarely accumulated for greater insights. This systematic review and meta-analysis quantifies the prevalence and characteristics of homicide victimization among older adults (65 years and older) compared with younger adults (18–64 years). Method: We searched Cumulative Index to Nursing and Allied Health Literature, Cochrane, Criminal Justice Abstracts, EMBASE, MEDLINE, ProQuest, PsycINFO, Scopus, and Web of Science for studies publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 73 publications
1
26
1
Order By: Relevance
“…The killing of an elderly female by a partner or family member represented the prevalent situation in the 2021 Italian female homicide data. This result is not consistent with the data in the study by Kennedy et al [ 28 ], who highlighted the presence of a stranger in almost a quarter of female homicide cases and noted crime to be a motive in the killing of approximately a third of elderly homicide cases. Our data may be explained by the low Italian homicide rate when compared with the rates of other crimes.…”
Section: Discussioncontrasting
confidence: 99%
“…The killing of an elderly female by a partner or family member represented the prevalent situation in the 2021 Italian female homicide data. This result is not consistent with the data in the study by Kennedy et al [ 28 ], who highlighted the presence of a stranger in almost a quarter of female homicide cases and noted crime to be a motive in the killing of approximately a third of elderly homicide cases. Our data may be explained by the low Italian homicide rate when compared with the rates of other crimes.…”
Section: Discussioncontrasting
confidence: 99%
“… 5 In 1996, the World Health Assembly (1996) called for violence research to be promoted as a public health research priority. 6 In 2015, it was estimated that 51 000 adolescents globally died from homicide, which was far more than the number of adolescent deaths from armed conflict (30 000), including war and internal unrest 7 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis reported a pooled older adult homicide rate of 2.02 per 100,000 [ 11 ], for the USA and other high-income Organisation for Economic Co-operation and Development (OECD) countries, and one that is lower than for younger adults aged 18–64 years (3.98 per 100,000). A study comparing mortality across the USA, Canada, Australia and New Zealand reported no decreasing trend in the older adult homicide rate between 2000 and 2012 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stereotypical older adult homicide victim has been characterised as an older woman who is killed in their home by a stranger [ 6 , 11 ]. In a recent meta-analysis, [ 11 ] the actual proportion estimate was lower for females than males (46.3 v 53.7%), and one-quarter (25.2%) were killed by family members, followed by strangers (24.2%), with an argument motive in 36.1% and a firearm mechanism in 24.5% of cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation